PERANAN INOVASI SEBAGAI MEDIATOR TERHADAP KINERJA USAHA KECIL MENENGAH ASESORIS GAWAI DI ROXY MAS JAKARTA - Christian, Michael; Merisa, Merisa (Jurnal Pengabdian dan Kewirausahaan, 2020)
Business performance is influenced by several factors, one of which is the innovation of sales ideas. Previous studies also explain the role of innovation in determining the performance of the business being undertaken. Some researches on the role of innovation in determining business performance emphasizes aspects of top management involvement, resources, existing technological capabilities and organizational culture. This research aims to analyse the determinants of business performance factors, especially on the role of innovation as a mediating factor. This research is quantitative using Partial Least Square (PLS)-Structural Equation Modelling (SEM) models. The results of this study explain that Innovation and Management Capability do not have an influence on business performance in the SME accessories gadget at ITC Roxy Mas. However, entrepreneurial orientation has an influence on business performance in the gadget accessories SMEs at ITC Roxy Mas. Furthermore, entrepreneurial orientation and management ability have an influence on innovation in the gadget accessories SMEs at ITC Roxy Mas. The results of the indirect effect explain the entrepreneurial orientation and management capabilities that are mediated by innovation do not have an influence on business performance in the gadget accessories SMEs at ITC Roxy Mas. Keywords: Business performance, SMEs, innovation, entrepreneurship